HUBUNGAN PENGETAHUAN ORANG TUA TENTANG KESEHATAN REPRODUKSI REMAJA DENGAN KEJADIAN PERNIKAHAN USIA DINI: The Relationship of Parental Knowledge about Adolescent Reproductive Health and The Incident of Early Marriage - Indah Ivo Reskika; Widyati Agustina; Nur Endah Sary Yessy (Forind Press, 2024)
Parents' knowledge about the age of marriage plays an important role in breaking the chain of cases of early marriage, for that parents must understand when the age of marriage is good. The purpose of the study was to analyze the relationship of parental knowledge about adolescent reproductive health with the incidence of early marriage. The design of this study is quantitative research with a correlational approach and includes crossectional research. The population in this study is parents who have teenagers and adolescents in Wanisodo Village, Bondowoso Regency with a total of 35 respondents. The sample size in this study was 35 people taken by random sampling. Data collection using questionnaires was then processed using SPSS using Chi Square Test. The results of data analysis found that most of them knew as many as 19 people (54.3%), most of them were low as many as 23 people (65.7%). There is a relationship between Parental Knowledge About Adolescent Reproductive Health and the Incidence of Early Marriage in Wanisodo Village, Grujugan District, Bondowoso Regency as evidenced by a significance value of 0.030 < 0.05, meaning that ho is rejected and ha is accepted, so there is a relationship between Parental Knowledge About Adolescent Reproductive Health and the Incidence of Early Marriage in Wanisodo Village, Grujugan District, Bondowoso Regency. It is recommended that youth posyandu be maximized.